2006
DOI: 10.1080/00365520600554550
|View full text |Cite
|
Sign up to set email alerts
|

Novel treatment in peritoneal adhesion prevention: Protection by polypeptides

Abstract: The intraperitoneal administration of poly-L-lysine and poly-L-glutamate resulted in a significant decrease in experimental postoperative peritoneal adhesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…In our early experiments we noted the optimal effect of the two oppositely charged polypeptides α-poly-L-lysine and poly-Lglutamate, which creates a matrix that serves as a mechanical barrier for adhesion formation [16]. Previous studies have also shown no effect on local immunological functions, i.e.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…In our early experiments we noted the optimal effect of the two oppositely charged polypeptides α-poly-L-lysine and poly-Lglutamate, which creates a matrix that serves as a mechanical barrier for adhesion formation [16]. Previous studies have also shown no effect on local immunological functions, i.e.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have also shown no effect on local immunological functions, i.e. peritoneal macrophages, and a local clearance of this biodegradable matrix within 4 weeks [16,19]. The antiadhesive effect of the polypeptides is based on electrostatic binding between the strong cation poly-L-lysine and the negatively charged damaged peritoneum [29], and thereafter electrostatic bonds between the poly-L-lysine and the anion poly-L-glutamate create a mechanical barrier between damaged and adhesionprone peritoneal tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations